Analysis of the Effect of Total Quality Management Implementation on Company Managerial Performance (Case Study: PT. X) - Wahyu Ismail Kurnia; Arfandi Ahmad; Muhammad Hasyim Tuankotta; Masurin Masurin (Journal of Industrial System Engineering and Management, 2022)
Optimization of the company's management quality performance is dependent on the accuracy of choosing the business strategy applied to the company. if improving the quality management of company only focuses on one aspect, then competitive advantage is very difficult to achieve. Total Quality Management (TQM) is one of the concepts of quality management improvement that considers all aspects of improving company performance. Therefore, this study aims to determine the implementation of TQM on managerial performance at PT. X. This company is the largest company in Eastern Indonesia, located in Makassar City and is engaged in the production of wheat flour. This study uses 3 of the 10 principles that exist in the TQM concept is customer focus, obsession with quality, education and training. The number of samples used as many as 120 respondents. The analytical method of this research uses a structural equation modeling (SEM) approach. The results showed that the implementation of Total Quality Management which describes the variables focused on customers, obsession with quality, education and training has an insignificant positive effect on managerial performance at PT. X. In addition, there is a direct effect of each TQM variable on the managerial performance variable